2018
DOI: 10.3389/fpubh.2018.00308
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of the Evidence on Health Promotion Interventions for Reducing Waterpipe Smoking: Implications for Practice

Abstract: Background: Waterpipe tobacco smoking is a traditional method of tobacco use, especially in the Eastern Mediterranean Region (EMR), but its prevalence is growing worldwide, especially among young people. Although often perceived as less harmful than other methods of tobacco use because the smoke passes through water, accumulating evidence shows harmful effects and that some smokers become addicted. Interventions that deglamourise and denormalise use have been recommended but little is known about the range and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…2 In the context of other waterpipe smoking interventions, our results are similar to those of a communitybased education and awareness intervention in Egypt 28 that had no impact on waterpipe smoking behaviours, but did have an effect on the awareness of the harms of waterpipe smoking. This suggests that future campaigns could be more effective if run in conjunction with other strategies, 13 which is in line with the comprehensive approach found to be most effective for tobacco control. 29 For example, our evaluation showed consistent low levels of awareness of support services for people who would like to quit smoking shisha, demonstrating the need for greater provision and promotion of support services for people who would like to reduce or quit waterpipe smoking.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…2 In the context of other waterpipe smoking interventions, our results are similar to those of a communitybased education and awareness intervention in Egypt 28 that had no impact on waterpipe smoking behaviours, but did have an effect on the awareness of the harms of waterpipe smoking. This suggests that future campaigns could be more effective if run in conjunction with other strategies, 13 which is in line with the comprehensive approach found to be most effective for tobacco control. 29 For example, our evaluation showed consistent low levels of awareness of support services for people who would like to quit smoking shisha, demonstrating the need for greater provision and promotion of support services for people who would like to reduce or quit waterpipe smoking.…”
Section: Discussionmentioning
confidence: 58%
“…A scoping review of health promotion interventions targeting waterpipe smoking found only 10 published intervention studies -5 policy interventions, 3 web-based educational interventions, 1 behavioural intervention, and only 1 community-level awareness campaign. 13,14 Given the lack of evidence-based interventions targeting waterpipe smoking, the 'Shisha No Thanks' project was a novel intervention that drew upon practices that have been used in other areas of tobacco control. The 'Shisha No Thanks' project was a codesign, social marketing health promotion campaign targeting waterpipe smoking among young people of Arabic speaking background in Sydney, Australia.…”
Section: Introductionmentioning
confidence: 99%
“…The use of clinician researchers, able to respond to identified health needs and provide culturally responsive and supported referrals, enhanced safety for these vulnerable families. In the Chinese Get Healthy Service (GHS) [ 41 , 42 ] and waterpipe smoking studies [ 43 , 44 ] (Tables 3 and 4 ), the research teams included one or more BRAs with established community networks who were trained in recruitment, consent and conduct of focus groups. BRAs also contributed to the validation and contextualization of research findings.…”
Section: Resultsmentioning
confidence: 99%
“…Shaping interventions to address waterpipe smoking in Arabic-speaking communities in Sydney, Australia: a qualitative study [ 43 , 44 ]…”
Section: Methodsmentioning
confidence: 99%
“…Finalmente, en la Fase Cinco, los resultados se resumen, se cotejan y se reportan [10][11] [18][19] , rehabilitación física [20][21] , sobrepeso y obesidad 22 , adicciones 23 , salud laboral 24 , cuidados intensivos 25 .…”
Section: Fases De La Metodología De La Rseunclassified